Inkuiri Studi Islam Anak Usia Dini - Fitriani, Wulan Fitri (Tasamuh: Jurnal Studi Islam, 2021)
Early childhood is children aged 0 - 6 years, where early childhood is the most important period in the formation of the basics of personality, thinking ability, intelligence, skills and social skills, this period requires conditions and stimulation in accordance with children's needs for growth and development is achieved optimally. The aspects of early childhood development according to the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 137 of 2013 include (1) Religious and moral values ​​(2) Motoric (3) Cognitive (4) Language (5) Social - Emotional and (6) ) Art. The first aspect of development that must be developed in early childhood is the aspect of religious and moral values ​​where early childhood is able to know Allah as its creator, the Prophet Muhammad as the messenger of the Islamic religion and Al-Quran as a guide for Islam. Religious values ​​must be instilled in early childhood as the initial foundation for children to live their lives. Islam as rahmatan lil'alamin must be studied in a clear and clear way. Various kinds of approaches are offered in understanding Islam, one of which is the inquiry approach, inquiry invites children to think critically and find their own answers to questions, formulate problems, formulate hypotheses systematically and analytically. It is hoped that they will be able to instill faith and devotion in children from an early age.